The Distribution, Excitation, and Formation of Cometary Molecules: Methanol, Methyl Cyanide, and Ethylene Glycol - Remijan, Anthony J; Milam, Stefanie N; Womack, Maria; Apponi, A. J; Ziurys, L. M; Wyckoff, Susan; A’Hearn, M. F; de Pater, Imke; Forster, J. R; Friedel, D. N; Palmer, Patrick; Snyder, L. E; et al. (The Astrophysical journal, 2008)
We present an interferometric and single-dish study of small organic species toward Comets C/1995 O1 (Hale-Bopp) and C/2002 T7 (LINEAR) using the BIMA interferometer at 3 mm and the ARO 12 m telescope at 2 mm. For Comet Hale-Bopp, both the single-dish and interferometer observations of CH sub(3)OH indicate an excitation temperature of [image] K and an average production rate ratio [image] at [image]1 AU. In addition, the aperture synthesis observations of CH sub(3)OH suggest a distribution well described by a spherical outflow and no evidence of significant extended emission. Single- dish observations of CH sub(3)CN in Comet Hale-Bopp indicate an excitation temperature of [image] K and a production rate ratio of [image] at [image]1 AU. The nondetection of a previously claimed transition of cometary (CH sub(2)OH) sub(2) toward Comet Hale-Bopp with the 12 m telescope indicates a compact distribution of emission, [image] (<8500 km). For the single-dish observations of Comet T7 LINEAR, we find an excitation temperature of CH sub(3)OH of [image] K and a CH sub(3)OH production rate ratio of [image] at [image]0.3 AU. Our data support current chemical models that CH sub(3)OH, CH sub(3)CN, and (CH sub(2)OH) sub(2) are parent nuclear species distributed into the coma via direct sublimation off cometary ices from the nucleus with no evidence of significant production in the outer coma.